Implementasi Jual Beli di Muka dalam Perspektif Syariah pada Bank dan Lembaga Keuangan Syariah - Razi Azwar Syahbudin Dalimunthe; Halimahtus Sakdiah Dalimuth; Abdul Nasser Hasibuan (Universitas Ichsan Sidenreng Rappang, 2025)
Forward sale (prepaid sale) is a form of transaction that involves payment in advance for goods or services that are agreed to be delivered at a later date. In the context of Islamic finance, the concept of forward sale serves as the foundation for several contracts, one of which is murabahah, the most commonly implemented contract in Islamic banking practices. Essentially, murabahah is a sales contract in which the seller discloses the cost price of an item and adds a mutually agreed profit margin. Thus, murabahah can be viewed as a specific form of forward sale that has been adapted to comply with sharia principles namely, the clarity of price, object, delivery time, and the absence of riba (usury) and gharar (uncertainty). This article aims to analyze the implementation of the murabahah contract from a sharia perspective in Islamic banks and financial institutions in Indonesia. The rapid growth of Islamic banking in Indonesia necessitates clarity in the concept and application of murabahah contracts to ensure compliance with Islamic law. The study employs a qualitative approach through literature review and analysis of policies and fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). The findings indicate that the practice of forward sale in the form of murabahah contracts can be implemented in accordance with sharia principles by emphasizing fairness, contract transparency, and supervision by the Sharia Supervisory Board (DPS) to ensure sharia compliance.